First, rewrite this expression as:
#2(x^2/x^4)(y/y^4)(z^-1/z^3)#
Next, use this rule of exponents to simplify the #x# term:
#x^color(red)(a)/x^color(blue)(b) = 1/x^(color(blue)(b)-color(red)(a))#
#2(x^color(red)(2)/x^color(blue)(4))(y/y^4)(z^-1/z^3) =>#
#2(1/x^(color(blue)(4)-color(red)(2)))(y/y^4)(z^-1/z^3) =>#
#2/x^2(y/y^4)(z^-1/z^3)#
Use this same rule to simplify the #z# term:
#2/x^2(y/y^4)(z^color(red)(-1)/z^color(blue)(3)) =>#
#2/x^2(y/y^4)(1/z^(color(blue)(3)-color(red)(-1))) =>#
#2/x^2(y/y^4)(1/z^(color(blue)(3)+color(red)(1))) =>#
#2/x^2(y/y^4)(1/z^4) =>#
#2/(x^2z^4)(y/y^4)#
Use this same rule and this rule to simplify the #y# term:
#a = a^color(red)(1)#
#2/(x^2z^4)(y/y^4) =>#
#2/(x^2z^4)(y^color(red)(1)/y^color(blue)(4)) =>#
#2/(x^2z^4)(1/y^(color(blue)(4)-color(red)(1))) =>#
#2/(x^2z^4)(1/y^3) =>#
#2/(x^2y^3z^4) =>#